Mudanças climáticas e recursos hídricos: percepções sobre riscos climáticos e capacidade adaptativa na região semiárida do Rio Grande do Norte, Brasil - Dias, Eric Mateus Soares (2020)
The water resources sector is considerably vulnerable and exposed to climate change. In the context of the Brazilian semi-arid region, water availability is quite limited by natural climatic conditions and anthropic action. This issue was studied in the context of the State of Rio Grande do Norte, whose semi-arid climate represents 93% of its territory and faces problems related to water availability that will be aggravated by climate change, thus requiring an improvement in management with an emphasis on climate adaptation. The objective of this dissertation was to analyze, through the perception of social and institutional actors, if the risks of climate change have been internalized in the management of water resources, in a way that allows the adaptive capacity in the semi-arid region of Rio Grande do Norte. The research adopted a qualitative approach, using bibliographic, documentary research and structured interviews as data collection techniques. 14 interviews were conducted with actors who can influence decision making on water issues in the State. The results show that the actors perceive the risks of climate change, especially in the sense of the worsening of natural climate threats that already occur in the region, however, the new risks that climate change imposes are not being internalized, which limits the capacity adaptive to answer them. However, despite the limitations in the management of water resources, it is considered that there are favorable elements for the development of adaptive capacity.